Curriculum Integration in Semi-Modern Pesantren: A Holistic Approach in Arabic Language Education - Hidayati, Hidayati; Muradi, Ahmad (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Purpose – This article analyzes the components and implementation of the Arabic curriculum at Pondok Pesantren Al-Hikmah Banjarmasin, focusing on how it addresses the evolving needs of students while integrating traditional Islamic knowledge with modern education. Design/methodology/approach – The research employs a qualitative descriptive approach, utilizing interviews, observations, and documentation to collect data. Findings- The findings reveal that the Arabic curriculum at the pesantren combines classical Islamic texts with general education, offering a balanced educational model. This integration allows students to understand religious texts in Arabic while acquiring modern knowledge. Despite the benefits, challenges arise in adapting to technological advancements and meeting the demands of a rapidly changing global context. The study also identifies that the curriculum model at Al-Hikmah aligns with a holistic approach, which integrates intellectual, spiritual, emotional, and physical development. The research highlights the need for continuous curriculum evaluation to ensure its relevance and effectiveness. Research Limitations/Implications – This study is limited by its specific focus on a single pesantren, which may not fully represent other pesantren models in the region. Further research is recommended to explore broader implications for the integration of Arabic language education within semi-modern pesantren systems.